Mucinous carcinoma of breast: A rare tumour with favorable prognosis - 10 years experience from a single center - Irfan Ul Islam Nasir; Haffsa Arif; Muhammad Fahd Shah; Awais Amjad Malik; Mariam Salim; Abdul Waheed Anwer; M Taqi Pirzada; Amina Iqbal Khan (Journal of Cancer and Allied Specialties, 2017)
Purpose: The purpose of this study was to describe the biological behaviour of mucinous breast carcinoma (MBC) regarding their clinical presentations, pathological features, prognosis and survival.